In vitro corrosion behavior of Mg‐5Zn alloy containing low Y contents. Issue 4 (12th August 2015) - Jafari, H.; Rahimi, F.; Sheikhsofla, Z.
Abstract : This study mainly investigated the impact of small amounts of yttrium (Y: 0.1–1.5 wt%) on in vitro corrosion behavior of Mg‐5Zn bioimplant alloy in simulated body fluid. Optical and scanning electron microcopies, energy dispersive X‐ray spectroscopy and X‐ray diffraction analysis were used to assess the microstructure of the alloys. Immersion and electrochemical tests were performed to investigate the degradation behavior of the alloys. Microstructural refinement was observed through increasing Y content, from 317 to 84 μm in grain size for Mg‐5Zn and Mg‐5Zn‐1.5Y alloys, respectively. Moreover, it was found that the addition of more than 0.3 wt% of Y forms I‐phase particles, whereas the content of 1.5 wt% Y forms I‐ and W‐ternary phases in Mg‐5Zn alloy. The results also showed that the addition of Y improves the corrosion behavior of Mg‐5Zn alloy, and the Mg‐5Zn‐0.7Y alloy was found to degrade more slowly than other alloys. This introduces Mg‐5Zn‐0.7Y alloy as a good candidate for bioimplant applications.